Education and social care predictors of offending trajectories: A UK administrative data linkage study - Hannah Dickson; George Vamvakas; Roxanna Short; Nigel Blackwood (International Journal of Population Data Science, 2023)
Objectives The age-crime curve indicates that criminal behaviour peaks in adolescence and decreases in adulthood, but longitudinal studies suggest that this curve conceals distinct patterns of (re)-offending or trajectories. Some trajectories (e.g., life course persistent offenders) are reported to have distinct risk factors and more negative outcomes than others (e.g., adolescent limited offenders).